Peningkatan Ekonomi Desa Sidorejo Kabupaten Bojonegoro melalui Industri Kreatif Berbahan Batang Pisang dan Komersialisasinya - Rima Fitria Adiati; Siti Nikmatin (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Lecturer service is an activity that disseminates research and innovation results to village communities. The program's main objective is to improve the economy of village communities in the creative consumer goods industry made from banana stem fiber. The implementation of the service includes interactive discussions and training in production and commercialization. The partner for this activity is the farmer group Karya Tani, which includes youth and homemakers in Sidorejo Village, Sukosewu District, and Bojonegoro Regency. The activity results are analyzed based on the increased knowledge and skills observed before and after the activity. The results show that society has experienced increased handicraft production to produce products with designs and variations that have high selling value. This can increase sales and the household economy by using local natural resources, especially banana stem waste.